The Effect of Discipline and Motivation on Employee Productivity at PT. Kereta Api Indonesia (Persero) Sintelis Divre III Palembang - Agustini, Triana; Subiyanto, Subiyanto; Widarti, Widarti; Desfitrina, Desfitrina; Ridwan, Muhammad (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
This study aims to determine the effect of discipline and motivation on employee productivity at PT. Kereta Api Indonesia (Persero) Sintelis Divre III Palembang. The method used is descriptive quantitative. Questionnaire is a data collection technique carried out by researchers to respondents who aim to obtain data or information related to the research topic. This study used a closed questionnaire form to make it easier for respondents to answer questions with the available choices. 4. Based on the test results of the coefficient of determination (Adjusted R Square) it is obtained at 0.619. This shows that work motivation and work discipline variables affect work productivity variables by 61.9%. While the remaining 38.1% is explained by other variables not examined in this study.